MICROBIAL OXIDATION OF FINASTERIDE WITH MACROPHOMINA PHASEOLINA(KUCC 730) - Erum, Saira; Sultan, Sadia; Shah, Syed Adnan Ali; Ashraf, Muhammad; Choudhary, Muhammad Iqbal (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objectives: New Â microbial oxidative derivatives of Finasteride [17Î²-(N-tert-butylcarbamoyl)-4-aza-5Î±-androst-1-en-3-one] (1) has been investigated with Macrophomina phaseolina (ATCC730). Methods: Fermented media of Â Macrophomina phaseolina (ATCC730) was prepared to cultivate the fungal cultures . Substrate 1 was incubated in liquid media for 16 days. After sixteen days, filtration and extraction of the fermented media was carried out with 9 L DCM in three portions. Resulting organic extract was dried using anhydrous (Na2SO4), and evaporated to afford a brown gum (950 mg). This on chromatographic purification with MeOH in CH2Cl2 afforded the metabolites 2-4 . Results: Three oxidised metabolites of finasteride (1) which were identified as 15-oxo-finasteride (2), 11a-hydroxyfinasteride (3), and 15Î²-hydroxyfinasteride (4). Metabolite 2 was found to be new. The structure of the oxidised metabolites were elucidated by 1-D (1H, 13C) and 2-D NMR (COSY, HMBC, HMQC, NOESY) techniques and MS analyses. Conclusion: As a result of these study, oxidation at C-7, C-11 and C-15 positions were found. Metabolite 2 was identified as a new metabolite.